2022
DOI: 10.3390/biomedicines10071677
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Derived Lung Tumoroids—An Emerging Technology in Drug Development and Precision Medicine

Abstract: Synthetic 3D multicellular systems derived from patient tumors, or tumoroids, have been developed to complete the cancer research arsenal and overcome the limits of current preclinical models. They aim to represent the molecular and structural heterogeneity of the tumor micro-environment, and its complex network of interactions, with greater accuracy. They are more predictive of clinical outcomes, of adverse events, and of resistance mechanisms. Thus, they increase the success rate of drug development, and hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 94 publications
0
5
0
Order By: Relevance
“…On the other hand, we must consider the genetic and epigenetic differences between cell lines and original tumors, which make it difficult to evaluate how much of the original tumor biology is retained in established cell line models that have been maintained long-term in vitro [19,20,57]. However, culturing cancer cells from human solid tumors has generally not been rapid or readily feasible because biopsy material is usually scant and it is difficult to eliminate CAFs [57].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, we must consider the genetic and epigenetic differences between cell lines and original tumors, which make it difficult to evaluate how much of the original tumor biology is retained in established cell line models that have been maintained long-term in vitro [19,20,57]. However, culturing cancer cells from human solid tumors has generally not been rapid or readily feasible because biopsy material is usually scant and it is difficult to eliminate CAFs [57].…”
Section: Discussionmentioning
confidence: 99%
“…The PDC obtained from a human biopsy of head and neck cancer tissue are referred to here as sample 1 (SP1) [23]. Primary HNSCC cells require specific culture medium and conditions to avoid cancer-associated fibroblast (CAF) overgrowth [20]. PNEU-medium provides a selection advantage to epithelial tumor cells and facilitates their proliferation so that they are not overgrown by CAFs [23].…”
Section: Intratumoral Melatonin Injection Reduces Tumor Growth In Pat...mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, having a co-culture of tumor cells together with fibroblasts and immunocytes could help achieve a higher fidelity platform. Quéméneur and others, indeed, successfully included fibroblasts and macrophages in a patient-derived tumoroid observing an enrichment in immune cells and obtaining the expression of the markers of lung adenocarcinoma ( Lê et al, 2022 ). These flourishing examples are paving the way for the use of tumoroid cultures in clinical trials as well as for basic research.…”
Section: Disease Modelingmentioning
confidence: 99%
“…As mentioned in our previous review, some limitations have been reported in the described lung cancer organoids (e.g., lack of cell types from the tumor microenvironment (TME)). To better optimize this, the use of autologous peripheral blood immune cells (PBMCs) will permit to maintain the TME complexity in vitro 21 . Co-culture of PDTs with PBMCs permit to address several points: (i) in ltration and tra cking in PDTs, and (ii) cytotoxicity activity of autologous immune cells.…”
Section: Introductionmentioning
confidence: 99%